TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP SISTEM PENJUALANBERJENJANG PADA PAYTREN PT. VERITRA SENTOSA INTERNASIONAL BANDUNG (STUDI MITRA PAYTREN DI PALU) - Nurul Wahidah (Tadayun: Jurnal Hukum Ekonomi Syariah, 2020)
The results of this study indicate that the PayTren tiered sales system in Palu has almost fulfilled the sales criteria in sharia economic law such as the fulfillment of pillars and requirements in selling and buying, there are no elements of maisir, immorality, or money games, there is no excessive sale of products that can harm. consumers, companies also provide ujrah according to the real work done by business partners, and there is no passive bonus. However, there are still elements of usury and gharar and the company has not yet fully provided comfort for its partners who make losses on the one hand.It is hoped that the company will pay more attention to and improve technicians in solving problems experienced by its partners and the company must also maintain a tiered sales system that is truly sharia in order to avoid buying and selling transactions that are prohibited by sharia. The partners are also expected to be able to maintain the good name of the company by always following the guidelines that have been made by the company and the regulations that apply in Indonesia.